Mobile Infrastructure Sharing - An Indian Scenario - Bora, Subhrajyoti (Prabandhan: Indian Journal of Management, 2011)
The paper focuses on the emerging trend on the Infrastructure Sharing Business of the Telecom Industry in the India Domain. Initially, all the telecom towers were maintained by the operators themselves, but now the trend is changing and the independent companies are coming up with the sole business of lending infrastructure and support to the telecom operators. This trend has changed the pattern of Initial Capital expenditure as well as the Operating expenditure of the operators. The paper also describes the auction policy of the Government of India for the 3G and BWA spectrum. The operators operating at the various circles along with various frequency bands are also taken care of. The actions of the regulatory bodies like the Telecom Regulatory Authority of India(TRAI) and the Department of Telecommunication has been controlling the regulatory issues and the way in which Indian Telecom will move in the future is much dependent on these apex bodies. Moreover, the synchronization of Indian regulatory issues with that of the International one is a must for the future. The study tries to find out the need of tower sharing in India along with the effort to find the future tower demands. The distinct functionalities of the Independent and the Operator owned tower companies will be vital for India’s Telecom growth and their requirements are looked into. Finally, focus has also been given towards the various advantages and disadvantages of the infrastructure sharing pattern evolving in India and the future course of action in that domain.